AMPA/kainate glutamate receptor antagonists prevent posttraumatic osteoarthritis - Bonnet, Cleo S.; Gilbert, Sophie J.; Blain, Emma J.; Williams, Anwen S.; Mason, Deborah J. (JCI Insight, 2020)
Musculoskeletal disorders represent the third greatest burden in terms of death and disability in the developed world. Osteoarthritis is the single greatest cause of chronic pain, has no cure, and affects 8.5 and 27 million people in the UK and US, respectively. Osteoarthritis is most prevalent in older people, but as it commonly occurs after joint injury, young people with such injuries are also susceptible. Painful joints are often treated with steroid or hyaluronic acid (HA) injections, but treatments to prevent subsequent joint degeneration remain elusive. In animals, joint injury increases glutamate release into the joint, acting on nerves to cause pain, and joint tissues to cause inflammation and degeneration. This study investigated synovial fluid glutamate concentrations and glutamate receptor (GluR) expression in injured human joints and compared the efficacy of GluR antagonists with current treatments in a mouse model of injury-induced osteoarthritis (ACL rupture). GluRs were expressed in the ligaments and meniscus after knee injury, and synovial fluid glutamate concentrations ranged from 19 to 129 μM. Intra-articular injection of NBQX (GluR antagonist) at the time of injury substantially reduced swelling and degeneration in the mouse ACL rupture model. HA had no effect, and Depo-Medrone reduced swelling for 1 day but increased degeneration by 50%. Intra-articular administration of NBQX modified both symptoms and disease to a greater extent than current treatments. There is an opportunity for repurposing related drugs, developed for CNS disorders and with proven safety in humans, to prevent injury-induced osteoarthritis. This could quickly reduce the substantial burden associated with osteoarthritis.